Association of advanced lung cancer inflammation index with all-cause and cardiovascular mortality in US patients with asthma - Li, Jiatao; Liu, Huanhuan; Xu, Bin (Frontiers in Nutrition, 2025)
BackgroundAsthma poses a significant global health challenge, representing a chronic respiratory disorder marked by airway inflammation. The advanced lung cancer inflammation index (ALI) served as a comprehensive index to assess inflammation. However, few studies have investigated the association between ALI and both all-cause and cardiovascular mortality in US patients with asthma.MethodsWe used data from the National Health and Nutrition Examination Survey (NHANES) to explore the association of ALI with all-cause and cardiovascular mortality in US patients with asthma. This study used Kaplan–Meier curves to examine the ALI index's impact on asthma patients' survival. We applied weighted Cox models and restricted cubic splines (RCS) analysis to assess the ALI-mortality link, identifying non-linear thresholds with a recursive algorithm. Subgroup analyses and sensitivity analyses were conducted, excluding those with missing covariates and cancer patients.ResultsA total of 6,211 asthma patients were enrolled and categorized into three groups based on ALI tertiles. The risk of all-cause mortality decreased as ALI increased in the fully adjusted multivariate Cox regression analysis; the hazard ratio (HR) is 0.95 (95% CI: 0.91–0.99, P = 0.01). Compared with the lowest ALI group, T1, the fully adjusted HR values for ALI and all-cause mortality in T2, T3 were 0.68 (95% CI: 0.55–0.85, P < 0.001), 0.53 (95% CI: 0.41–0.68, P < 0.001). The risk of cardiovascular mortality was also lower in the groups of T2 (HR: 0.84, 95% CI: 0.55–1.28) and T3 (HR: 0.47, 95% CI: 0.31–0.71, P for trend < 0.001), respectively. In addition, the results of the subgroup analyses were robust.ConclusionsThis cohort study demonstrated the higher accuracy of ALI in predicting mortality in asthma patients, highlighting its important clinical value of ALI in risk assessment and prognosis evaluation.